2011
DOI: 10.1123/ijsnem.21.2.113
|View full text |Cite
|
Sign up to set email alerts
|

Regular Dark Chocolate Consumption’s Reduction of Oxidative Stress and Increase of Free-Fatty-Acid Mobilization in Response to Prolonged Cycling

Abstract: This study investigated the effects of regular consumption of dark chocolate (DC), rich in cocoa polyphenols, on plasma metabolites, hormones, and markers of oxidative stress after prolonged exhaustive exercise. Twenty active men cycled at 60% maximal oxygen uptake (VO2max) for 1.5 hr, with the intensity increased to 90% VO2max for a 30-s period every 10 min, followed by a ride to exhaustion at 90% VO2max. In the 2 wk before exercise participants consumed 40 g of DC or an isocarbohydrate-fat control cocoa liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
70
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 44 publications
10
70
2
Order By: Relevance
“…Despite differences in plasma glucose between treatments all measured glucose responses were euglycemic (>4 mmol), and thus it may not be surprising that the current study found no differences in ~11.5 min TT performance, which is consistent with a recent publication showing no change in a time to exhaustion performance test over ~6.5 min after chronic and acute dark chocolate consumption (Allgrove, Farrell et al 2011). Consequently, perhaps a more taxing and prolonged exercise stimulus may have altered the performance outcomes.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…Despite differences in plasma glucose between treatments all measured glucose responses were euglycemic (>4 mmol), and thus it may not be surprising that the current study found no differences in ~11.5 min TT performance, which is consistent with a recent publication showing no change in a time to exhaustion performance test over ~6.5 min after chronic and acute dark chocolate consumption (Allgrove, Farrell et al 2011). Consequently, perhaps a more taxing and prolonged exercise stimulus may have altered the performance outcomes.…”
supporting
confidence: 80%
“…However, very few studies have examined metabolic and anti-fatigue effects of dark chocolate. Recent studies have shown that 100 g of dark chocolate increased the concentration of plasma glucose (Davison et al 2011), and chronic dark chocolate consumption caused a ~21% increase in plasma free-fatty acids (Allgrove et al 2011), during prolonged exercise compared to a iso-fat/calorie/carbohydrate (CHO) control. But, these studies did not examine mechanisms associated with these shifts in metabolism during exercise, nor performance outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Latter studies have mostly supported a protective relationshipe between cocoa or chocolate consumption and a variety of health indicators [14] . The results of these studies have shown that cocoa and DC consumption can reduce stress, stimulate brain function, fight cancerous cells, improve circulation, mood, memory, immune system, and even protect the heart [12] , and liver tissue [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Dark chocolate for management of NAFLD rich in bioflavonoids (flavanols, polyphenols, and theobromine) [12] , which has the highest antioxidant level in comparison with other food sources based on Oxygen Radical Absorbance Capacity measurement [13] . Besides nutrients such as saturated fat (60%), monounsaturated fat (35%), and linoleic acid (3%), chocolate contains important minerals such as potassium and magnesium [14] as well as cocoa, which is the main and the quintessential ingredient in chocolate [10] .…”
Section: Introductionmentioning
confidence: 99%